Response of tomato to innovative organo-mineral fertilizers - Sitzmann, Tomas Javier; Alpigiano, Andrea; Lerda, Cristina; Moretti, Barbara; Zavattaro, Laura; Grignani, Carlo (Frontiers in Sustainable Food Systems, 2024)
Organo-mineral fertilizers (OMFs) with low organic carbon (Corg) content have been associated with a higher mineral fraction nutrient use efficiency. However, peat extraction from endangered ecosystems, typically used in this type of OMF, mineralizes long-time stored Corg. This study analyses replacing peat in OMFs with biowaste materials –considered byproducts decomposed by microorganisms and other living things. The study investigated three stabilized biowaste –GC (green compost from pruning residues), MSWC (municipal solid waste compost), and VC (manure-based vermicompost) –as the organic matrixes for granular OMFs, in which they are impregnated with dissolved ammonium sulfate and urea while coating diammonium phosphate granules. Each OMF contained 7.5% Corg, 20% mineral N, and 10% mineral P2O5 (OMF20-10). A high nutrient concentration has the advantage of requiring low OMF application volumes. The biowaste OMFs were compared with a peat OMF with the same Corg-N-P2O5 concentration. Peat and MSWC were also used to create OMFs containing 7.5% Corg, 10% mineral N, and 5% mineral P2O5 (OMF10-5). A 75-day tunnel trial was conducted under semi-controlled conditions using tomato (Solanum lycopersicum L.) fertilized to an equivalent of 81 mg N kg-1soil and 18 mg P kg-1soil. Controls included no fertilization (N0P0) and a mineral N and P fertilization (MFNP). The SPAD, BBCH indexes, and shoot numbers were measured weekly. The berry and total aboveground yield, N and P uptakes, and N and P use efficiencies (NUE and PUE, respectively) were calculated at harvest. All treatments outperformed the control N0P0 in most indicators. Peat20-10 did not have more berry yield than other OMF20-10; however, the higher number of shoots indicated a higher potential yield in case of prolonging the experiment. At the end of the 75 days, VC20-10 and MSWC20-10 showed PUE similar to Peat20-10, suggesting that those materials can be replaced. In the case of OMF10-5, MSWC10-5 had yield and N and P uptakes like peat OMFs, confirming a potential use of MSWC as peat replacement even at different nutrient concentrations. This research provides evidence of the effectiveness of biowaste OMFs, offering a positive outlook for sustainable agriculture. However, their use is not recommendable for short growing seasons.